2009
DOI: 10.1111/j.1365-2966.2009.15913.x
|View full text |Cite
|
Sign up to set email alerts
|

Lyα absorbers in motion: consequences of gravitational lensing for the cosmological redshift drift experiment★

Abstract: The evolution of the expansion rate of the Universe results in a drift in the redshift of distant sources over time. A measurement of this drift would provide us with a direct probe of expansion history. The Lyman α (Lyα) forest has been recognized as the best candidate for this experiment, but the signal would be weak and it will take next generation large telescopes coupled with ultrastable high‐resolution spectrographs to reach the cm s−1 resolution required. One source of noise that has not yet been assess… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Such new prospects lately prompted renewed interest in the theoretical predictions of the redshift variation in different scenarios (see e.g. [20][21][22][23][24][25][26][27][28][29]).…”
Section: The Redshift Driftmentioning
confidence: 99%
“…Such new prospects lately prompted renewed interest in the theoretical predictions of the redshift variation in different scenarios (see e.g. [20][21][22][23][24][25][26][27][28][29]).…”
Section: The Redshift Driftmentioning
confidence: 99%
“…The translational motion of a gravitational system makes a difference on the propagation of electromagnetic signals, which is the so-called velocity effect [1,2]. The issue of velocity effects on the gravitational frequency shift of light was discussed in many papers [2][3][4][5][6][7][8][9][10][11]. Birkinshaw and Gull [3] studied the transversal velocity effect of cluster of galaxies and showed that the gravitational frequency shift of light is proportional to the low transverse lens velocity and the deflection angle of light.…”
Section: Introductionmentioning
confidence: 99%
“…However, even with future precision radio telescopes, the measurement of the SL effect represents a difficult enterprise [27] as it demands several years of observation (usually some decades) to register enough signal-to-noise ratio so as to yield a possible reliable detection of the cosmological redshift drift signal. Best candidate objects for a feasible detection of this faint signal are good Hubble flow tracers as far as possible [28].…”
Section: Introductionmentioning
confidence: 99%